2017
DOI: 10.3390/ijms18102121
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxic Effects of Short-Term Doxorubicin Administration: Involvement of Connexin 43 in Calcium Impairment

Abstract: The use of Doxorubicin (DOXO), a potent antineoplastic agent, is limited by the development of cardiotoxicity. DOXO-induced cardiotoxicity is multifactorial, although alterations in calcium homeostasis, seem to be involved. Since even the Connexin43 (Cx43) plays a pivotal role in these two phenomena, in this study we have analyzed the effects of DOXO on Cx43 expression and localization. Damage caused by anthracyclines on cardiomyocytes is immediate after each injection, in the present study we used a short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 51 publications
4
33
0
Order By: Relevance
“…Lurtz and Louis reported that the gap junction‐mediated cell‐to‐cell transfer of dye between lens epithelial cells or Cx43‐transfected HeLa Cells was inhibited by Ca 2+ /CaM (Lurtz & Louis, , ). Moreover, the rapid onset of GJIC inhibition (within seconds) suggested that this inhibition was mediated by the direct interaction of CaM with one or more of the lens connexins, rather than by the action of a CaM‐dependent protein kinase (Lurtz & Louis, , ; Pecoraro et al, ). According to our results and those of previous studies, we hypothesize that CaM is involved in the decrease of GJIC induced by BaP via directly interacting with Cx43, rather than by altering the expression of Cx43 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lurtz and Louis reported that the gap junction‐mediated cell‐to‐cell transfer of dye between lens epithelial cells or Cx43‐transfected HeLa Cells was inhibited by Ca 2+ /CaM (Lurtz & Louis, , ). Moreover, the rapid onset of GJIC inhibition (within seconds) suggested that this inhibition was mediated by the direct interaction of CaM with one or more of the lens connexins, rather than by the action of a CaM‐dependent protein kinase (Lurtz & Louis, , ; Pecoraro et al, ). According to our results and those of previous studies, we hypothesize that CaM is involved in the decrease of GJIC induced by BaP via directly interacting with Cx43, rather than by altering the expression of Cx43 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 phosphorylation is mechanistically linked to gap junctional communication, and phosphorylation of Cx43 at different sites controls gap junction assembly, gap junction size and gap junction turnover (Zou et al, ). In addition, intracellular Ca 2+ homeostasis is important in the maintenance of normal cellular functions in response to extracellular stimuli, and is also a regulatory mechanism of GJIC (Pecoraro et al, ; Zhou et al, ). However, whether BaP can induce changes in GJIC level in Sertoli cells through the two mechanisms described above remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported on the widening of the QRS complex following DOX exposure, which suggested intraventricular conduction defects due to myocardial ultrastructural changes, such as intercalated disc separation, myo brillar derangement, vacuolization, and interstitial edema [11,17]. Furthermore, Pecoraro et al demonstrated that DOX treatment resulted in markedly reduced expression and function of connexin-43, which potentially leads to slower conduction velocity and loss of rapid electrical synchronization throughout the myocardium [18]. However, there are inconsistent ndings in the literature.…”
Section: Qrs Complex Duration and Amplitude Changementioning
confidence: 99%
“…Despite the enormous amount of research in this area, the exact molecular mechanisms underlying the toxic effects of doxorubicin on the heart are still an area that warrants further investigation. Analysis of the literature data suggests that the mechanisms of doxorubicin's cardiotoxicity are multifactorial (Renu et al, 2018;Wenningmann et al, 2019) and include the impairment of mitochondrial energetics, increase of reactive oxygen species (ROS) leading to oxidative stress, cell necrosis and induction of pro-apoptotic signaling pathways (Chaudhari et al, 2017;Pecoraro et al, 2017;Delehanty et al, 2018).…”
Section: Introductionmentioning
confidence: 99%